Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s0104-11692006000100017
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção de lesões de pele no perioperatório: revisão integrativa da literatura

Abstract: Nursing decision making in daily practice needs to be based on scientific knowledge. Evidence-based practice establishes the use of research results in clinical practice, with integrative literature review as one of its resources. This integrative review aimed to find and evaluate the available evidence on efficient nursing care interventions for the prevention of skin injuries in surgical patients, during or as a result of the perioperative period. To select the articles, we used two databases, Cinahl and Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
0
237

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(399 citation statements)
references
References 19 publications
0
124
0
237
Order By: Relevance
“…An analogous phase to collecting the conventional survey data. For data collection of articles it was used a validated instrument containing the following items: identification of the original article, methodological characteristics of the study, assessment of the methodological rigor of measured interventions and results found [8].…”
Section: Methodsmentioning
confidence: 99%
“…An analogous phase to collecting the conventional survey data. For data collection of articles it was used a validated instrument containing the following items: identification of the original article, methodological characteristics of the study, assessment of the methodological rigor of measured interventions and results found [8].…”
Section: Methodsmentioning
confidence: 99%
“…4 th ) Categorization of studies. This step is considered similar to the collection of conventional data, for which we used a tool [6] that allows the researcher to evaluate, individually, selected studies, analyzing them methodologically and in relation to synthesis of the findings. Thus, studies were listed through a careful reading and inclusion criteria chosen.…”
Section: Methodsmentioning
confidence: 99%
“…For this, we used a previously validated instrument [14], containing the following items: identification of the original article, methodological characteristics of the study, assessment of the methodological rigor of measured interventions and findings. Thus, it was possible individualized analysis of each study, making it possible to sort them and synthesize them categorically.…”
Section: Stage 4: Categorization Of Selected Studiesmentioning
confidence: 99%